Current thermal state of permafrost and potential impact on the El Niño Southern Oscillation (ENSO) in the Southern Peruvian Andes - Yoshikawa, Kenji; Úbeda Palenque, José; Masías Alvarez, Pablo Jorge; Pari Pinto, Walter; Apaza Choquehuayta, Fredy Erlingtton; Vásquez Choque, Estibene Pool; Ccallata Pacsi, Beto; Concha Niño de Guzmán, Ronald Fernando; Luna, Gonzalo; Iparraguirre, Joshua; Ramos, Isabel; De la Cruz, Gustavo; et al. (2018)
Tropical, high-mountain permafrost has a unique thermal regime due to its exposure to strong solar radiation and to the rougher surface snow morphology (due to an increased occurrence of penitentes -- that is, snow spikes and ridges ranging from centimeters to meters in height) which reduce convective sensible heat transfer from the surface. Latent heat transfer and higher albedo occurring during the wet season contributes to positive feedback that supports the presence of permafrost. This preliminary study reports on the thermal state of Peruvian permafrost. It evaluates the potential combined impact of the El Niño Southern Oscillation (ENSO), along with the eleven-year solar cycles of Coropuna (15°32′S; 72°39′W; 6,377 m a.s.l.), and the Chachani volcanic complexes (16°11′S; 71°31′W; 6,057m a.s.l.); both mountains are located in the western Central Andes (e.g., west edge of the Altiplano). Temperature monitoring boreholes were established at 5217m on Coropuna and 5331m at Chachani, and electric resistivity was surveyed to better understand permafrost spatial distribution in these locations. This seven-year record of permafrost temperature data encompasses historically extreme El Niño and La Niña events. Our results show that the current lower-altitude permafrost boundary (ca. 5100m) is critically influenced by the balance of wet and dry seasons: permafrost tends to deplete during drought years. Typical permafrost thickness was 10-20 m and contained ice-rich pore spaces. The presence of permafrost and its thermal resistance depends on ice content and on higher albedo, usually due to pyroclastic materials (especially pumice) which are ideal materials for supporting permafrost resilience.